Financial impact and effect on the outcome of preoperative tests for at‐risk older hip fracture patients. Issue 6 (7th March 2018) - Steinberg, Ely L; Warschawski, Yaniv; Elis, Jacob; Rotman, Dani; Rachevsky, Gil; Factor, Shai; Salai, Moshe; Ben‐Tov, Tomer
Abstract : Aim: Older patients with proximal femoral fractures often undergo preoperative tests due to coexisting morbidities. Our aim was to evaluate these tests and their impact on patient outcome and medical expenses. Methods: This retrospective study includes data on head computed tomography, carotid ultrasound, echocardiography and pulmonary functional tests calculated according to the type of surgery (osteosynthesis or hip arthroplasty) carried out on 2798 patients. Time‐to‐surgery, test repeated postoperatively, American Society of Anesthesiology Physical Status score, additional procedures, hospitalization time, 30‐day mortality and associated medical expenses were evaluated. Results: A total of 921 preoperative tests were carried out in 780 (28%) patients, and 375 postoperative tests were carried out in 329 (12%) patients ( P < 0.001). A total of 23 procedures were carried out after surgery, none related to the originally carried out tests. Significant group differences were found for American Society of Anesthesiology Physical Status score, days to surgery, hospitalization time (days) and mortality rates. The medical expenses of these tests were 1.3% of the average income per case, and 0.6% of the average study group income. Conclusions: Non‐routine preoperative tests prolong time‐to‐surgery, increased hospitalization time and contribute to 30‐day mortality. No postoperative procedure was related to preoperative test findings. The financial cost for these tests does not burden the medical expenses per procedure.Geriatr Gerontol Int 2018; 18: 937–942 .